Extracorporeal Life Support during Cardiac Arrest Resuscitation in a Porcine Model of Ventricular Fibrillation - Reynolds, Joshua C. (J Extra Corpor Technol, 2013)
Implementation barriers for extracorporeal life support in out-of-hospital cardiac arrest (OHCA) include initiation delay and candidate selection. We explored ischemia duration, cardiopulmonary resuscitation (CPR) duration, and physiologic variables that discriminated animals with return of spontaneous circulation (ROSC). We instrumented eight female swine (31.9 ± 9.8 kg) with femoral artery and external jugular vein cannula. After 8 (n = 4) or 15 (n = 4) minutes ventricular fibrillation (VF), animals received 30, 40, 50, or 60 minutes of CPR and then drugs (.6 U/kg vasopressin, .1 mg/kg epinephrine, .1 mg/kg propranolol, sodium bicarbonate as indicated) after 5 minutes of CPR. Extracorporeal membrane oxygenation (ECMO) flow rate was 3 L/min ≤2 hours and then 1.5 L/min ≤2 hours before weaning. Animals were defibrillated (150 J biphasic) ≥15 minutes ECMO. Primary outcome for successful resuscitation was ROSC (organized rhythm with systolic blood pressure >80 mmHg). We measured arterial blood gas, electrolytes, mean arterial pressure (MAP), coronary perfusion pressure (CPP), and five quantitative VF waveform measures at key intervals. Continuous variables were compared with two-sample t test. All 8-minute VF animals were successfully resuscitated and had ROSC. MAP was higher at the beginning (27.0 ± 7.1 vs. 15.0 ± 4.4; p = .03) and end (31.3 ± 12.8 vs. 11.5 ± 7.3; p = .03) of CPR in animals successfully resuscitated. CPP was higher at the beginning of CPR (11.9 ± 4.6 vs. 3.3 ± 2.2; p = .01) and the end of CPR (18.5 ± 12.1 vs. .9 ± 1.4; p = .03) among animals with ROSC. Amplitude spectrum area (AMSA) was superior at the end of CPR (–2.0 ± 1.8 vs. –5.0 ± 1.4; p = .04) in animals successfully resuscitated. In a porcine OHCA model, MAP and CPP at the beginning and end of CPR were higher in animals successfully resuscitated. AMSA was superior at the end of CPR in animals successfully resuscitated.